PERANCANGAN PEMBANGKIT LISTRIK TENAGA SURYA PADA ROOFTOP KANTOR PT BALI CUKUP MANDIRI - Sankhya Pranata Adiguna, I Made; Setiawan, I Nyoman; Dwi Giriantari, I. A. (Jurnal SPEKTRUM, 2023)
Solar Power Plant is a power generator that converts sunlight into electricity. Solar Power Plant has a simple concept, namely converting sunlight into electrical energy. These solar cells can produce unlimited energy directly taken from the sun, and do not require fuel, so solar cells are often said to be clean and environmentally friendly. This journal discusses how to design a Solar Power Plant system at PT Bali Cukup Mandiri. The design is in the form of calculating the number of solar panels that can be installed, the capacity obtained, calculating the required capital costs, choosing the appropriate type of Solar Power Plant, the profit and loss if the Solar Power Plant is installed, and a comparison of electricity costs before and after it is installed. The simulation results of Solar Power Plant electrical energy production using the Helioscope and HOMER applications. The calculation results for the Solar Power Plant system for a capacity of 8 kWp require 24 units of 335 Wp solar modules, using a Solar Power Plant installation system of 24 serial units, the capital cost for making Solar Power Plant is around Rp. 114,504,000 electricity generated by the PV system is 13,337 kWh/year and accommodates up to 49% of electrical energy. savings of IDR 16,303,604 in one year after deducting the total electricity bill payments. The total time needed to cover the initial investment in designing a rooftop solar system at PT Bali Cukup Mandiri is 8 years.